Cyber security threats and challenges facing human life - Shekokar, Narendra M.; Vasudevan, Hari (Engineer); Durbha, Surya Srinivas; Michalas, Antonis; Nagarhalli, Tatwadarshi P.; Mangrulkar, Ramchandra; Mangla, Monika (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Cyber Security Threats and Challenges: A Comprehensive Coverage proposes to provide a comprehensive view of the issues, threats, and challenges that are faced in the cyber security domain with a detailed analysis of effective countermeasures and mitigations. The financial sector, Healthcare, digital manufacturing and social media are some of the important areas where cyber-attacks are frequent and cause great harm. Hence, special emphasis will be given to study and analyze the cyber security challenges and countermeasures in these three important areas, apart from other sectors"--
Cyber security challenges in digital manufacturing and possible ways of mitigation -- An efficient proxy signature based authority delegation scheme for medical cyber physical system -- The impact of COVID-19 pandemic on cybersecurity issues of healthcare domain : a scoping review -- Cyber threats : a fear over industries -- A comprehensive survey of existing security techniques in IoT protocol stack -- Impact of cyber security threats on IoT applications -- Need of Internet of Things (IoT) forensics : case studies and analysis -- A comparative analysis of tree based algorithms and application of XGBoost classifier in malware detection -- An assessment on game-based cyber defense strategy for SDN -- Smart computing -- cyber threats and mitigation techniques -- SQL injection attacks on Indian websites : a case study -- Information security systems and its future -- Different similarity measures for secure name matching in record linkage.
OCLC-licensed vendor bibliographic record.
Keywords: Computer security; Computer networks -- Security measures; Computer crimes -- Prevention; COMPUTERS / Computer Engineering; COMPUTERS / Networking / Security; COMPUTERS / Internet / Security